An Experimental Study of the Carbonation of Serpentinite and Partially Serpentinised Peridotites - Lacinska, Alicja M.; Styles, Michael T.; Bateman, Keith; Hall, Matthew; Brown, Paul D. (Frontiers in Earth Science, 2017)
In situ sequestration of CO2 in mantle peridotites has been proposed as a method to alleviate the amount of anthropogenic CO2 in the atmosphere. This study presents the results of 8-month long laboratory fluid-rock experiments on representative mantle rocks from the Oman-United Arab Emirates ophiolite to investigate this process. Small core samples (3 cm long) were reacted in wet supercritical CO2 and CO2-saturated brine at 100 bar and 70°C. The extent of carbonate formation, and hence the degree of carbon sequestration, varied greatly depending on rock type, with serpentinite (lizardite-dominated) exhibiting the highest capacity, manifested by the precipitation of magnesite MgCO3 and ferroan magnesite (Mg,Fe)CO3. The carbonate precipitation occurred predominantly on the surface of the core and subordinately within cross-cutting fractures. The extent of the CO2 reactions appeared to be principally controlled by the chemical and mineralogical composition of the rock, as well as the rock texture, with all these factors influencing the extent and rate of mineral dissolution and release of Mg and Fe for subsequent reaction with the CO2. It was calculated that ≈0.7 g of CO2 was captured by reacting ≈23 g of serpentinite, determined by the mass of magnesite formed. This equates to ≈30 kg CO2 per ton of host rock, equivalent to ≈3% carbonation in half a year. However, recycling of carbonate present in veins within the original rock sample could mean that the overall amount is around 2%. The increased reactivity of serpentinite was associated with preferential dissolution of more reactive types of serpentine minerals and brucite that were mainly present in the cross-cutting veins. The bulk of the serpentinite rock was little affected. This study, using relatively short term experiments, suggests that serpentinite might be a good host rock for CO2 sequestration, although long term experiments might prove that dunite and harzburgite could be as effective in an engineered system of CCSM. Wet scCO2 proved to be chemically more aggressive than CO2-saturated brine and its ingress along fractures and grain boundaries resulted in greater host rock dissolution and subsequent carbonate precipitation.